2009
DOI: 10.1105/tpc.109.069815
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisTic62 and Ferredoxin-NADP(H) Oxidoreductase Form Light-Regulated Complexes That Are Integrated into the Chloroplast Redox Poise  

Abstract: Translocation of nuclear-encoded preproteins across the inner envelope of chloroplasts is catalyzed by the Tic translocon, consisting of Tic110, Tic40, Tic62, Tic55, Tic32, Tic20, and Tic22. Tic62 was proposed to act as a redox sensor of the complex because of its redox-dependent shuttling between envelope and stroma and its specific interaction with the photosynthetic protein ferredoxin-NADP(H) oxidoreductase (FNR). However, the nature of this close relationship so far remained enigmatic. A putative additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 62 publications
(95 reference statements)
8
131
0
Order By: Relevance
“…Two proteins have recently been reported to bind FNR at the thylakoid membrane in Arabidopsis: TROL (Juric et al, 2009) and Tic62 (Benz et al, 2009). Blue native-PAGE analysis has shown that TROL binds FNR to complexes of ;140 to 190 kD, and Tic62 binds FNR into several complexes at higher molecular masses.…”
Section: Differences In Maize Fnr Recruitment Into Arabidopsis Thylakmentioning
confidence: 99%
See 3 more Smart Citations
“…Two proteins have recently been reported to bind FNR at the thylakoid membrane in Arabidopsis: TROL (Juric et al, 2009) and Tic62 (Benz et al, 2009). Blue native-PAGE analysis has shown that TROL binds FNR to complexes of ;140 to 190 kD, and Tic62 binds FNR into several complexes at higher molecular masses.…”
Section: Differences In Maize Fnr Recruitment Into Arabidopsis Thylakmentioning
confidence: 99%
“…Approximate molecular masses are given in kilodaltons to the left of the blot, and FNR-containing complexes coordinated by Tic62 and TROL are indicated to the right of the blot. (Benz et al, 2009;Juric et al, 2009), there has been much speculation that FNR bound to different protein complexes, and in the soluble phase, might coordinate different electron transfer processes Joliot and Johnson, 2011). As we found Arabidopsis plants expressing maize FNR1, FNR2, and FNR3 are respectively enriched in FNR bound to TROL, Tic62, and in soluble FNR, we compared their PET capacity, to gain further insight into this question.…”
Section: Fnr Location Influences Electron Transport Around the Photosmentioning
confidence: 99%
See 2 more Smart Citations
“…Tic110, Tic20 and Tic21 have been suggested to function as the protein translocation channel of the inner envelope 1,2,7,8 . Several stromal proteins, including chaperones, proteases and redox regulators, are also involved in the import process 6,9,10 . The stromal domain of Tic110 and Hip/Hop domain of Tic40 may function as scaffolds that tether stromal chaperones, including Hsp93 and Hsp70, which facilitate protein translocation across the inner membrane 2,6,11 .…”
mentioning
confidence: 99%